PERBANDINGAN VEGETASI TUMBUHAN BAWAH DI BAWAH EMPAT JENIS TEGAKAN HUTAN TANAMAN DI CANDIKUNING, BALI - MUSTAID SIREGAR (BERITA BIOLOGI, 1987)
MUSTAID SIREGAR. 1987.The comparison of ground vegetation under four forest plantations in Candikuning, Bali. Suppl. BeritaBiologi. 3: 45-50.The ground vegetation under four forest plantations of different species in Candikuning (Altingia excelsa, Manglietia glauca, Agathis dammara, Pinus merkusiij have been investigated by using quadrat method. The results showed that the highest index of similarity was 53,06% between A. dammara and P. merkusii plantations, and the lowest index of similarity was 18,21% between A. excelsa and P. merkusii plantations. The species composition and community stability of these ground vegetations under "each plantation differed. The community of ground vegetation under A.excelsa plantation was more diverse and stable than the others. The ground vegetation under M. glauca, A.dammara and P.merkusii plantations were dominated by herbs, while under A. excelsa plantation were dominated by seedling of trees, that originated from A. excelsa stand and others surrounding tree species.